Antimicrobial activity of cream incorporated with silver nanoparticles biosynthesized from Withania somnifera - Marslin, Gregory (2015)
We report on the antimicrobial activity of a cream formulation of silver nanoparticles (AgNPs), biosynthesized using Withania somnifera extract. Aqueous extracts of leaves promoted efficient green synthesis of AgNPs compared to fruits and root extracts of W. somnifera. Biosynthesized AgNPs were characterized for their size and shape by physical-chemical techniques such as UV-visible spectroscopy, laser Doppler anemometry, transmission electron microscopy, scanning electron microscopy, atomic force microscopy, X-ray diffraction, and X-ray energy dispersive spectroscopy. After confirming the antimicrobial potential of AgNPs, they were incorporated into a cream. Cream formulations of AgNPs and AgNO3 were prepared and compared for their antimicrobial activity against human pathogens (Staphylococcus aureus, Pseudomonas aeruginosa, Proteus vulgaris, Escherichia coli, and Candida albicans) and a plant pathogen (Agrobacterium tumefaciens). Our results show that AgNP creams possess significantly higher antimicrobial activity against the tested organisms.